Synthesis and characterization of bile acid-based poly beta amino esters for paclitaxel delivery - Gangwal, Jitendra J.; Kulkarni, Mohan G. (Journal of Applied Polymer Science, 2011)
New biodegradable poly beta amino esters were synthesized by the polymerization of Deoxycholic acid (DOCA) in all the structural planes by 1, 4 addition of Trimethylene dipiperidine (TMDP) to diacrylates of Deoxycholyl glycol, Methyl deoxycholate and Trimethylolpropane deoxycholate esters. H-1-NMR, C-13-NMR and IR studies confirmed presence of amine and Deoxycholyl units in polymers. XRD and TGA studies indicated that all the polymers were amorphous and thermostable up to 300 degrees C. DSC studies revealed glass transition temperature (T-g) in the range 70-80 degrees C. All the polymers degraded very slowly in the buffers of pH 1.1, 7.4 and 10 because of the hydrophobic nature of Deoxycholate units. These polymers also exhibited pH sensitivity due to the incorporation of amines along with Deoxycholate units in the backbone. P-Nitroaniline (PNA) release followed anomalous release kinetics. Paclitaxel (PTX) loaded nanospheres prepared from these polymers were spherical and uniform in the size range 75-250 nm and 0.4-1 mu depending upon the method of preparation. PTX loading was in the range 60-90%, while release (up to 20-60%) was sustained over a period of 100 h. (c) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 220-232, 2011
Keywords: bile acid; biodegradable; Nanoparticles; Paclitaxel; poly beta amino esters